2010
DOI: 10.1029/2009jd013263
|View full text |Cite
|
Sign up to set email alerts
|

Dust aerosol optical properties retrieval and radiative forcing over northwestern China during the 2008 China‐U.S. joint field experiment

Abstract: The Atmosphere Radiation Measurements Program's Ancillary Facility (AAF/SMART‐COMMIT) was deployed to Zhangye (39.082°N, 100.276°E), which is located in a semidesert area of northwest China, during the period of late April to mid June in 2008. We selected 11 cases to retrieve dust aerosol optical depth (AOD), Angstrom exponent, size distribution, single‐scattering albedo (SSA) and asymmetry parameter (ASY) from multifilter rotating shadowband radiometer (MFRSR) measurements. These cases are dominated by large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 70 publications
(73 reference statements)
9
111
2
Order By: Relevance
“…Huang et al (2009) found that the single scattering albedo (SSA) of Taklamakan dust aerosols is about 0.89 at 0.67 µm which is about 6% less than for Saharan dust. Ge et al (2010) also confirmed that the SSA shows an increasing trend with wavelength, indicating stronger dust aerosol absorption at shorter wavelengths. The values of SSA, which range from 0.76 ± 0.02 to 0.86 ± 0.01, are much lower than those derived in Africa and also relatively smaller than earlier results obtained over East Asia.…”
Section: Analysis and Resultssupporting
confidence: 70%
“…Huang et al (2009) found that the single scattering albedo (SSA) of Taklamakan dust aerosols is about 0.89 at 0.67 µm which is about 6% less than for Saharan dust. Ge et al (2010) also confirmed that the SSA shows an increasing trend with wavelength, indicating stronger dust aerosol absorption at shorter wavelengths. The values of SSA, which range from 0.76 ± 0.02 to 0.86 ± 0.01, are much lower than those derived in Africa and also relatively smaller than earlier results obtained over East Asia.…”
Section: Analysis and Resultssupporting
confidence: 70%
“…The relative difference in the mean SSA between adjusted and unadjusted value is about 4 % in MAM. Compared with the SSA observed at the other observatory over the Loess Plateau (Ge et al, 2010), the values of the SSA (adjusted) are larger in this study. The adjusted ASY at 500 nm ranges from 0.65 to 0.74 in MAM (not shown in figure).…”
Section: Comparison Between the Observed And Simulated Radiative Fluxesmentioning
confidence: 67%
“…Bi et al (2010) analyzed the aerosol optical properties measured at Semi-Arid Climate and Environment Observatory of Lanzhou University over Loess Plateau of Northwestern China obtained through a CIMEL Sun photometer of the ground-based Aerosol Robotic Network for the period of August 2006-October 2008. However, there are some difference between the results of Ge et al (2010) and Bi et al (2010). This study will use another measurement (sky-radiometer) to calculate and check the optical and radiative properties of the dust aerosol at SACOL over Loess Plateau of Northwest China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated retrieval error of MODIS aerosol products are known to be = ±0.03 ± 5% over the ocean and = ±0.05 ± 15% over the land (Remer et al 2005). However, over the land, instead of the MODIS standard product of "dark-target" approach (Kaufman et al 1997), we used the "Deepblue" product (Hsu et al 2004) claimed to be in better agreement with ground-based observations (Ge et al 2010). Meanwhile, CALIPSO AOT shows a systematic underestimation compared with MODIS AOT (Royer et al 2010;Kacenelenbogen et al 2011;Yumimoto et al 2008).…”
Section: Model Validationmentioning
confidence: 99%